Effects of the pitch surface on displacement of youth players during soccer match-play - Brito, A.; Roriz, P.; Silva, P.; Duarte, R.; Garganta, J. (Journal of Human Kinetics, 2018)
The aim of this study was to analyze the effect of different pitch surfaces (artificial turf, natural turf and dirt field) on positioning and displacement of young soccer players (age: 13.4 ± 0.5 yrs; body height: 161.82 ± 7.52 cm; body mass: 50.79 ± 7.22 kg and playing experience: 3.5 ± 1.4 yrs). Data were collected using GPS units which allowed to calculate spatial distribution variability, assessed by measuring entropy of individual distribution maps (ShannEn). Ellipsoidal areas (m2) representing players` displacement on the pitch, centred on the average players` positional coordinates, were also calculated, with axes corresponding to the standard deviations of the displacement in the longitudinal and lateral directions. Analysis of variance (ANOVA) was used to evaluate differences between pitch surfaces and across players` positions. There was significant effect in positioning (?2 = 0.146; p < 0.001) and displacement (?2 = 0.063; p < 0.05) by the players between pitch surfaces. A dirt field condition induced an increase in the players` movement variability, while players` displacement was more restricted when playing on artificial turf. Also, there were significant effects on positioning (?2 = 0.496; p < 0.001) and displacement (?2 = 0.339; p < 0.001) across players` positions. Central midfielders presented the greatest movement variability and displacement while fullbacks showed the lowest variability. Subsequently, the results may contribute to implement strategies that optimise players` performance in different surface conditions.